Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Terumbu Karang Melalui Proses Hidrotermal Dengan Variasi Rasio Ca/P Dan pH Reaksi - Muhammad Khairil Amri; Yelmida Azis; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hydroxyapatite (HAp, Ca10(PO4)6(OH)2) is one of the calcium phosphate compounds which is the main inorganic component of composing human hard tissue such as bones and teeth. Hydroxyapatite (HAp) is a material used as bone implant, adsorbent and catalyst. The purpose of this study was to determine the effect of variations in the Ca/P ratio (1.57; 1.67 and 1.77) and reaction pH (9, 10 and 11) to degree of hydroxyapatite crystallinity, and compare the results of XRD hydroxyapatite characterization on the variations carried out. The research begins with the calcination process of coral reefs to form CaO which is made into PCC using the carbonation method. Coral PCC and (NH4)2HPO4 were reacted using hydrothermal vessels with variations in the Ca/P ratio (1.57; 1.67 and 1.77) and mixing pH of reactants at (9, 10 and 11), reaction time for16 hours at 140oC. The synthesis results will be analyzed using X-Ray Diffractometer (XRD) and Scanning Electron Microscopy (SEM-EDX) and Brunaeur-Emmet-Teller (BET). The hydroxyapatite results were obtained on the condition of 1.67 Ca / P ratio and pH 11 with a crystal diameter of 26.91 nm, crystallinity degree of 74.55%, final Ca / P ratio of 1.66 and wide surface which is 27,003 m² / g.Keywords: hydroxyapatite, hydrothermal, carbonasi, precipitate calcium carbonate